Differential Diagnosis of Dizziness in Patients Who Had Carotid Vertebral Artery Doppler for Arterial System Diseases - , Kübra Aktan Gökduman, Muratcan Gökduman, Fazıl Necdet Ardıç, Mohammad Alşalaldeh (Turkish Journal of Gastroenterology 1, 2023)
Background: Carotid vertebral Doppler ultrasonography (CVDU) is performed frequently in patients with dizziness. If a pathology is discovered, usually, it is accepted as a cause of dizziness. Our objective was to investigate the ratio of dizziness in patients tested with CVDU for arterial system diseases and make differential diagnoses of dizziness for its real cause. Methods: A total of 195 patients undergoing CVDU were included. Among them, 20 patients reported dizziness and were referred for further examination, while the remaining 175 patients were included as controls. Advanced balance tests were performed for a differential diagnosis of dizziness. The two groups were then compared in terms of carotid narrowing, intima–media thickness (IMT), and vertebral artery resistive index (RI). Results: Among the dizziness patients, 10 exhibited abnormal IMT, 11 showed a pathological vertebral artery resistive index, and 6 had carotid narrowing. However, when comparing the control group with the vertigo group, no signifcant differences were found in terms of pathological values observed in CVDU (P > .05). Within the vertigo group, the causes were further categorized: Ten patients had evident peripheral disease, 2 had migraine vestibulopathy, 1 had persistent postural-perceptual dizziness (3PD), 2 had orthostatic hypotension, and 1 had congenital nystagmus. One patient was considered to have vertebrobasilar insuffciency, and 3 patients were suspected to have central vascular pathology. Conclusion: It was known that several patients who sought medical attention due to vascular disease also reported experiencing dizziness. However, it was determined that most dizziness cases were unrelated to vascular disease. Cite this article as: Aktan Gökduman K, Gökduman M, Ardıç FN, Alşalaldeh M. Differential diagnosis of dizziness in patients who had carotid vertebral artery Doppler for arterial system diseases. ENT Updates. 2023;13(3): 51-56.